Assessment of variation in the fiber characteristics of the wood of vitex doniana sweet and its suitability for paper production (2014)
The study investigated the fibre characteristics and chemical composition of Vitex doniana towards determining its potentials for pulp and paper. Fibre dimensions are of great importance because of the strong correlation between it and the strength properties of wood and paper. Axial and radial examinations of fibre characteristics of naturally grown wood of Vitex doniana were investigated to determine its suitability for paper production. Wood slivers were prepared from slices, introduced into wash bottles containing equal volume (1:1) of glacial acetic acid and 30% hydrogen peroxide and investigated on a Rheichert Visopam microscope. Variations existed in the axial and radial direction of the wood. The mean values of fibre characteristics are: fibre length (1.48mm), fibre diameter (21.9μm), fibre lumen width (12.7μm) and fibre wall thickness of Vitex doniana was 4.9μ. The mean lignin, cellulose and extractive contents were 28.1%, 41.2% and 3.5% respectively. Based on the derived values: Slenderness ratio, flexibility coefficient and Runkel ratio, species of Vitex doniana were considered to be good paper making materials.